Awareness of cervical cancer and willingness to be vaccinated against human papillomavirus in Mozambican adolescent girls - Bardají, Azucena (Papillomavirus Res, 2018)
Sub-Saharan Africa concentrates the largest burden of cervical cancer worldwide. The introduction of the HPV vaccination in this region is urgent and strategic to meet global health targets. This was a cross-sectional study conducted in Mozambique prior to the first round of the HPV vaccine demonstration programme. It targeted girls aged 10–19 years old identified from schools and households. Face-to-face structured interviews were conducted. A total of 1147 adolescents were enrolled in three selected districts of the country. Most girls [84% (967/1147)] had heard of cervical cancer, while 76% believed that cervical cancer could be prevented. However only 33% (373/1144) of girls recognized having ever heard of HPV. When girls were asked whether they would accept to be vaccinated if a vaccine was available in Mozambique, 91% (1025/1130) answered positively. Girls from the HPV demonstration districts showed higher awareness on HPV and cervical cancer, and willingness to be vaccinated. This study anticipates high acceptability of the HPV vaccine in Mozambique and high awareness about cervical cancer, despite low HPV knowledge. These results highlight that targeted health education programmes are critical for acceptance of new tools, and are encouraging for the reduction of cervical cancer related mortality and morbidity in Mozambique.